Knockdown of PIK3R6 impedes the onset and advancement of clear cell renal cell carcinoma - Jia Yang; Xiaoni Zhong; Xiaoling Gao; Wenyi Xie; Yaokai Chen; Yuanjiang Liao; Peilin Zhang (Cell Adhesion & Migration)
In this research, we investigated the role of PIK3R6, a regulatory subunit of PI3Kγ, known for its tumor-promoting properties, in clear cell renal cell carcinoma (CCRCC). Utilizing the UALCAN website, we found PIK3R6 upregulated in CCRCC, correlating with lower survival rates. We compared PIK3R6 expression in CCRCC tumor tissues and adjacent normal tissues using immunohistochemistry. Post RNA interference-induced knockdown of PIK3R6 in 786-O and ACHN cell lines, we performed CCK-8, colony formation, Edu staining, flow cytometry, wound healing, and transwell assays. Results showed that PIK3R6 silencing reduced cell proliferation, migration, and invasion, and induced G0/G1 phase arrest and apoptosis. Molecular analysis revealed decreased CDK4, Cyclin D1, N-cadherin, Vimentin, Bcl-2, p-PI3K and p-AKT, with increased cleaved caspase-3, Bax, and E-cadherin levels in CCRCC cells. Moreover, inhibiting PIK3R6 hindered tumor growth. These findings suggest a significant role for PIK3R6 in CCRCC cell proliferation and metastasis, presenting it as a potential therapeutic target.